The Lead Letter of Pistos from Patraeus - Zavoykina, Natalia; Pavlichenko, Natalia (Hyperboreus, 2019)
In 2012 in the part of ancient Greek settlement Patraeus submerged by the waters of the Taman Bay (the modern village Garkusha of the Krasnodar Kray, Russia) a lead letter was found. The letter belongs to the category of business correspondence and contains a list of debtors with enumeration, in decreasing order, of the sums to be exacted. The gold staters mentioned in the letter are most likely kyzikenoi. In addition, the letter contains an accusative of a personal name that has not been encountered before: Σαπασιν (Σαπασις, Σαπασιος?).